A Compact Wideband SIW Bandpass Filter For UWB Applications - Pavithra, A.; Suvitha, S.; Megala, J. (International Journal of Engineering and Technology, 2018)
In this paper wideband Band Pass Filter is proposed using vertical array of vias in split ring resonator for UWB applications. As frequency of operation increases microstrip devices are not efficient because of its small wavelength and it requires very tight tolerances for manufacturing. Waveguide devices are preferred at high frequency, however their manufacturing process is difficult. Therefore a new design guiding architecture called Substrate Integrated Waveguide(SIW) is proposed. A typical SIW is designed by using geometrical parameters. The performance of SIW-BPF has been analysed for different via diameters by maintaining the pitch ratio between 0.4 and 0.8. Proposed filter provides return loss of greater than 10 dB and insertion loss of 0 dB. Designed filter is simulated using ADS software.Â